2022
DOI: 10.1038/s41467-022-34983-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibody responses to SARS-CoV-2 variants in Australian children

Abstract: There is limited understanding of antibody responses in children across different SARS-CoV-2 variants. As part of an ongoing household cohort study, we assessed the antibody response among unvaccinated children infected with Wuhan, Delta, or Omicron variants, as well as vaccinated children with breakthrough Omicron infection, using a SARS-CoV-2 S1-specific IgG assay and surrogate virus neutralization test (% inhibition). Most children infected with Delta (100%, 35/35) or Omicron (81.3%, 13/16) variants serocon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Serological samples prior to the Omicron infection were available from 15 children of whom 4 were SARS-CoV-2 seronegative (primary infection) and 11 seropositive (secondary infection). Primary Omicron infection elicited low antibody titres against both the ancestral spike and RBD domains ( Figure 1A, Extended Data Figure 2A ), consistent with previous reports ( 18 ). Titres against Delta variant were high in one child, likely due to subclinical Delta infection between blood sampling, and as such this was regarded as a secondary infection ( Extended Data Figure 2A ).…”
Section: Resultssupporting
confidence: 90%
“…Serological samples prior to the Omicron infection were available from 15 children of whom 4 were SARS-CoV-2 seronegative (primary infection) and 11 seropositive (secondary infection). Primary Omicron infection elicited low antibody titres against both the ancestral spike and RBD domains ( Figure 1A, Extended Data Figure 2A ), consistent with previous reports ( 18 ). Titres against Delta variant were high in one child, likely due to subclinical Delta infection between blood sampling, and as such this was regarded as a secondary infection ( Extended Data Figure 2A ).…”
Section: Resultssupporting
confidence: 90%
“…In unvaccinated children, infected with the ancestral, Delta or Omicron variants and children with at least one dose of vaccine and a breakthrough Omicron infection, children who were both vaccinated and infected had higher neutralizing capacity against the ancestral variant than children who were unvaccinated but infected with the ancestral, Delta, or Omicron variants. 69 This confirms the concept that hybrid immunity generates more potent antibody responses than infection alone. Amongst children who were infected with the Omicron variant, vaccinated children also had a significantly higher neutralization response against Omicron than unvaccinated children.…”
Section: Hybrid Immunitysupporting
confidence: 73%
“…This has been well documented in adults 47 , 48 , 49 , 50 and recently explored in children with hybrid immunity. 51 , 52 We tested the sera of children with breakthrough infection (visit 5, n = 25) and vaccinated-only children (visit 3, n = 134, including data from an extended cohort; Table 2 ) with a surrogate virus neutralisation test (sVNT) 53 to assess their ability to inhibit the binding of hACE2 to wildtype S-RBD and variant S-RBD (Alpha/B.1.1.7, Beta/B.1.351, Gamma/P.1, Delta/B.1.617.2, Delta+/B.1.617.2.1, Lambda/C.37, Mu/B.1.621, and Omicron/B.1.1.529, Omicron sublineages BA.2/BA.5, XBB, XBB.1.5 and SARS-CoV-1). We confirmed that sera of children with hybrid immunity had a strongly improved capacity to cross-neutralise SARS-CoV-2 variants over children with non-hybrid immunity from vaccination alone ( Fig.…”
Section: Resultsmentioning
confidence: 99%